PENGARUH PENAMBAHAN TEPUNG GAPLEK SEBAGAI BAHAN ADITIF TERHADAP KUALITAS SILASE AMPAS TEBU - Wardani, Dewi Risma; Aswana, Aswana; Supriyono, Supriyono; karmila, yeni (Universitas Muara Bungo, 2025)
This research aims to determine the physical quality, pH and dry ingredients of bagasse silage with the addition of cassava flour as an additive. The research was carried out in the basic laboratory of Muara Bungo University from 26 June 2024 to 17 July 2024. The design in this study was a completely randomized design (CRD) with 4 treatments and 5 replications, including T0 (sugar bagasse silage without the addition of cassava flour additive), T1 (sugar bagasse silage with the addition of 2% cassava flour additive), T2 (sugar bagasse silage with the addition of cassava flour additive 3%), T3 (sugar bagasse silage with additional cassava flour additive 4%), T4 (sugar bagasse silage with additional cassava flour additive 5%). The parameters of this research are physical quality which includes color, aroma and texture, and pH and dry matter. The research results showed that color, aroma, texture and pH had a very significant effect (P0.01), while dry ingredients showed no significant effect (P 0.05).